On Norman Mailer’s “The White Negro” (1957): More Than Six Decades Later - Andrew Urie (European Journal of American Studies)
This article engages in an examination of Norman Mailer’s fascinating yet problematic essay “The White Negro” (1957). Drawing from humanities and social sciences perspectives, I employ an interdisciplinary approach that historically contextualizes Mailer’s essay while also examining how it continues to speak to contemporary American racial, cultural, economic, and socio-political issues.